Self-Poisonings by Use of ‘Suicide Kits’ and a ‘Home-Made’ Multi-Xenobiotics Mixes: Are They a Growing Problem in Forensic Toxicology? - Karolina Nowak; Paweł Szpot; Agnieszka Chłopaś-Konowałek; Kaja Tusiewicz; Olga Wachełko; Marcin Zawadzki (Proceedings, 2024)
Year by year, the field of psychiatry faces an escalating crisis, particularly concerning children and adolescents [...]